929 LEADLESS PACEMAKER IMPLANTATION FOLLOWING TRANSVENOUS LEAD EXTRACTION: DATA FROM HIGH-VOLUME REFERRAL CENTERS. (15th December 2022) - Mitacchione, Gianfranco; Schiavone, Marco; Arabia, Gianmarco; Gasperetti, Alessio; Denora, Marialessia; Arosio, Roberto; Palmisano, Pietro; Montemerlo, Elisabetta; Manuel, Cerini; Russo, Giulia; Mazzone, Patrizio; Ziacchi, Matteo; et al.
Abstract: Background: limited data on real-world safety and efficacy of leadless pacemakers (LPMs) in patients who underwent transvenous lead extraction (TLE) are currently available. The present study aims to assess long-term safety and efficacy of LPMs implantation following TLE, compared with LPM de novo implant patients. Methods: consecutive patients who underwent LPM implantation in 12 centers joining the International LEAdless PacemakEr (i-LEAPER) registry were enrolled end retrospectively considered. Patients receiving LPM following TLE (n=184) were compared with patients with de novo implant (n=995). The primary endpoint was LPM-related complications rate at implant and during follow-up (FU). Additionally, differences in electrical performance were assessed between the two groups. Results: 1179 patients were enrolled in this study and followed for a median of 33 months. LPM related major complications and all-cause mortality did not differ among the two groups (1.6% TLE group vs. 2.2% de novo group, p=0.785, and 5.4% TLE group vs . 7.8% de novo group, p=0.288, respectively). Pacing threshold (PT) resulted higher in the TLE group throughout the whole follow-up (FU) (Figure 1). Higher PTs were recorded in LPMs implanted at same location from where the previous transvenous lead was removed, as far as 24-months postimplant (Figure 2), with a higher proportion of patients with high PT (>1 to 2V @0.24ms) in the first group at implant, 1-month, and 12-month FU (Figure 3). Conclusion: In this real-world registry, LPMs showed a satisfactory safety and efficacy profile after TLE. In the post-TLE cohort, better electrical parameters were obtained when LPMs were implanted at a different location from where the previous transvenous lead was extracted.